(untitled) (Annals of Medical Research, 2021)
Aim: Interest in facial morphology continues to increase due to its importance in establishing identity within the human population among other things. This study was conducted to establish nasofacial and canthal types in indigenes of Benue State in Central Nigeria. Materials and Methods: Measurements of face height and width, nasal height and width and inner and outer canthal distances were taken from a sample of 210 subjects (mean age 23.11±3.45 years). The measurements were made using a 30cm sliding calipers and a 150mm electronic digital caliper. Results: Showed that mean facial height and width in males were 110.40±8.50mm and 132.16±7.15mm respectively while females had 103.61±7.60mm and 128.32±6.95mm correspondingly. Consequently, the facial form for both genders was euryprosopic. Mean nasal height in males was 42.99±3.94mm while mean nasal width was 41.59±5.07mm. Similarly, mean nasal height in females was 39.39±3.82mm and mean nasal width was 38.44±4.43mm. The resulting nasal type was platyrrhine in both males and females. Mean inner and outer canthal distances in males were found to be 33.63±3.61mm and 104.20±9.11mm respectively. In females, these distances were found to be 32.68±3.39 and 102.71±5.76 respectively. Accordingly, closed type of canthal index was established.Conclusion: Both genders had the same face, nose and canthal types. Sexual dimorphism exists in the measured parameters, except with inner and outer canthal distances.